PP29 The paramedic will see you now: understanding new roles in primary care. Issue 10 (25th September 2020) - Porter, Alison; Driscoll, Timothy; Edwards, Adrian; Evans, Bridie; Griffiths, Lesley; Hussain, Ather; James, Mari; Jones, Jenna; Keen, Leigh; Kingston, Mark; Phillips, Ceri; Snooks, Helen; et al.
Abstract : Background: In response to rising healthcare demand and shortages of general practitioners (GPs), policy across the UK supports paramedics joining the clinical team in primary care. Numbers of paramedics in primary care (PPC) are increasing in England and Wales through a range of local initiatives. As the first stage in the ARRIVE feasibility study evaluating PPC, we conducted preliminary qualitative research to: Understand the key components of the PPC intervention and its potential impacts Identify sites with PPC and describe the range of existing interventions Develop a logic model to describe PPC. Methods: We interviewed a total of 19 stakeholders from across Wales, including Health Board managers, GPs, practice managers and paramedics. Interviews were recorded and transcribed in full, then analysed thematically. We held a stakeholder event, bringing together 21 people involved in commissioning, planning and delivering PPC to discuss the key components of a logic model, including outcome measures for evaluation. Results: We developed a logic model describing how paramedics provide direct clinical contact with patients in a primary care setting. Potential positive impacts include better patient experience, reductions in emergency admissions through better proactive care, increased sustainability of primary care, and increased levels of clinical skills and satisfaction for paramedics. Components of the intervention which varied across sites included type of patient contact (home visit or surgery); approaches to patient selection and triage; employment model; training and induction; and clinical supervision and support from GPs. Implications: PPC is a rapidly developing area of provision in primary care, but there is great variation in the nature of models which have been implemented, and there is still uncertainty about the risks and benefits of PPC, and about how best to deliver it. Our logic model underpins the ARRIVE feasibility study, which will help to build the evidence base urgently needed on the PPC innovation.